2020
DOI: 10.2147/ndt.s265194
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of <em>Apolipoprotein E</em> Gene Polymorphism with Ischemic Stroke in Coronary Heart Disease Patients Treated with Medium-intensity Statins</p>

Abstract: Objective To study the association of apolipoprotein E ( APOE ) gene polymorphism with ischemic stroke (IS) in coronary heart disease (CHD) patients treated with medium-intensity statins. Methods The retrospective study was performed on 662 samples including 169 CHD subjects complicated with IS, 296 subjects with CHD, and 197 control subjects. The APOE gene was obtained from case files. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Ischemic stroke, the most common type of a stroke, is a complex multifactorial disease caused by the interaction between environmental risk factors and genetic predisposition [ 17 , 18 , 19 ]. To date, numerous case-control studies have confirmed the association between SNPs and a stroke [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Ischemic strokes occurring in the carotid circulation are the most common type of an ischemic stroke, accounting for approximately 85% of all cases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke, the most common type of a stroke, is a complex multifactorial disease caused by the interaction between environmental risk factors and genetic predisposition [ 17 , 18 , 19 ]. To date, numerous case-control studies have confirmed the association between SNPs and a stroke [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Ischemic strokes occurring in the carotid circulation are the most common type of an ischemic stroke, accounting for approximately 85% of all cases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of statin treatment were found in ApoE4 carriers by most authors [ 183 - 186 ]. Mixed or negative effects were found in a few studies [ 187 , 188 ]. ApoE genotype had no significant effect on the response to treatment with atorvastatin in patients with heterozygous familial hypercholesterolemia [ 188 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ε 4 allele was referred to be an important risk factor for cerebral infarction [ 14 – 16 ]. E3/E4 genotype and the ε 4 allele were related to the incidence of IS among coronary heart disease patients receiving statin therapy [ 38 ]. On the contrary, we found that ApoE allele distribution has no association with IS risk in T2DM subjects.…”
Section: Discussionmentioning
confidence: 99%